Description Of Community Knowledge About Flood Disaster Preparedness in Jajar Village Magetan Regency - Kartika, Apridika Ajeng; Prajayanti , Eska Dwi (Jurnal Multidisiplin, 2026)
Floods are frequent natural disasters that have significant impacts on communities, especially in flood-prone areas. Community preparedness is a crucial factor in reducing the risk and impact of floods, which is influenced by the level of community knowledge. Objective: To determine the level of community knowledge about flood disaster preparedness, describe the characteristics of respondents, and describe community knowledge in Jajar Village. Method: This study employed a quantitative descriptive method through a cross-sectional approach. The sample was selected using purposive sampling and calculated using the Slovin Formula, with a total sample of 72 respondents from the Jajar Village community. Data collection was conducted using a flood disaster preparedness knowledge questionnaire. Results: The study revealed that 40 respondents (55.6%) had good knowledge of flood preparedness, 26 respondents (36.1%) had fair knowledge, and 6 respondents (8.3%) had poor knowledge. Conclusion: The level of public knowledge regarding flood disaster preparedness in Jajar Village is mostly in the good category with 40 respondents (55.6%).